A study of the effects of blended learning on university students' critical thinking: A systematic review - Alireza Mortezaei Haftador; Banafsheh Tehranineshat; Zahra Keshtkaran; Zinat Mohebbi (Wolters Kluwer Medknow Publications, 2023)
One of the basic, constructive needs of humans, which plays a major part in their development is critical thinking. As education is one of the factors in shaping individuals' critical thinking, the present study addresses the effects of blended learning and its subcategories on university students' critical thinking (and its subcategories). The present article is a review study. Data were collected using valid search engines and databases. The keywords which were used included blended learning, integrated learning, blended training, integrated training, critical thinking, critical thinking disposition, and critical thinking skills, as well as the subcategories of blended learning, that is, the flex model, the self-blended model, the enriched virtual model, and the rotation model and its subcategories (the station rotation model, the lab rotation model, the flipped classroom model, and the individual rotation model). The results of 14 sources, out of the selected 15 sources, showed that blended learning and its subcategories, that is, the flex model, the self-blended model, the enriched virtual model, and the rotation model and its subcategories contribute to university students' critical thinking of disposition and skill. One of the essential skills which must be given more serious attention in learning in the twenty-first century is critical thinking. Having the benefits of both lecturing and e-learning, blended learning is a more effective and practical method for promoting critical thinking in university students.